A Study On Artificial Intelligence In Smart Cities For On-Demand Vehicle Automation Systems (Cuestiones de Fisioterapia, 2023)
Urban planning is becoming much easier and more familiar because to ai. Those who reside in cities are more likely to be prepared for future problems and to stay up with the newest innovations in problem-solving strategies compared to those who live in rural areas. Experts anticipate that by the year 2050, metropolitan areas will be home to the vast majority of the global population. Ensuring that public transport systems in metropolitan areas are not only reliable but also safe and easy to use is crucial. Fifty research publications on urban mobility considering ai, the iot, and communication and information technologies make up this review. In these pieces, we zero in on how these three disciplines meet. The articles were published in a variety of journals between 2015 and 2024. Two of the most crucial considerations in selecting the papers were the presentation's clarity and the presenter's energy. Intelligent routing systems, prediction algorithms, and real-time traffic signal optimisation are the main focusses of this group's research. The widespread use of autonomous vehicles has the potential to improve public transportation, lessen traffic congestion, and raise road safety standards. Not only that, but this is demonstrated by a plethora of additional criteria that are not limited to those already mentioned. In order to address many problems, it is crucial to apply ai to smart cities and urban transportation. Issues such as the digital divide across nations are examples of what this topic encompasses.